GE_GERICHTE P/29506/2024 vom 7. Mai 2025 - GE Cour de justice (2025)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;INFRACTIONS CONTRE L'HONNEUR;SECRET DE FONCTION | CPP.310.al1.leta; CPP.310.al1.letc; CP.52; CP.173; CP.174